Progress in achieving household food security in climate-smart villages in the Albertine Rift, western Uganda - Recha, John W.M.; Radeny, Maren A.O.; Kimeli, Philip; Hafashimana, David; masanyu, Julius; Ssekiwoko, Fred; Odongo, William (2016)
Hoima is located in western Uganda east of Lake Albert, on a landscape that is generally undulating with relatively flat low lying area alternating with broad hills. The area has a population density of 160 persons per square kilometer, with 22% of the people living below the poverty line. The area faces land degradation and declining soil fertility. The key food crops are cassava, beans, sweet potatoes, and maize. Chicken, pigs, cows and goats are important for food and income generation. Most households get their food supplies from their own farms throughout the year. The worst months for food supplies, when more than 20% of households get their food mainly from off-farm sources and 40% of the households have food deficits are March and April, which also mark the beginning of the rains after several months of dry season. About 31% of households are food secure all year long. Another 35% suffer food deficits for 1-2 months per year. 16% of these households struggle to get enough to feed their families for 3-4 months, 9% for 5-6 months, and 10% for more than six months per year.